Нові можливості оздоровчого харчування з позицій нутригенетики та нутригеноміки - Сімахіна, Галина Олександрівна; Науменко, Наталія Валентинівна (My University, 2025)
У роботі на основі літературних даних показано, що врахування нутригеномних і нутригенетичних властивостей оздоровчих продуктів та натуральних дієтичних добавок дасть можливість у недалекому майбутньому істотно підвищити ефективність їх застосування для поліпшення стану здоров’я населення, подовження тривалості активного життя громадян, зміцнення генофонду української нації.

The work, based on literature data, shows that taking into account the nutrigenomic and nutrigenetic properties of health products and natural dietary supplements will make it possible in the near future to significantly increase the effectiveness of their use to improve the health of the population, extend the duration of active life of citizens, and strengthen the gene pool of the Ukrainian nation.
Now there are continuing the theoretical and experimental studies in the field of healthy nutrition and its ability to enhance the body mechanisms to get adapted to the malignant environmental factors and thenceforth to get ready for self-regulation and self-restoration. The other trends are the identification of the essential nutrients to make the special healthy influence on the body; the search for the new natural sources, including those nontraditional, to create the healthy foodstuffs and natural food supplements containing the biologically active components capable of ‘turning on’ or ‘turning off’ the certain genes, dependently on the body issues. The authors of this article displayed the fact that, taking into consideration the nutrigenomic and nutrigenetic properties of foodstuffs and natural food additives, it would be possible in the nearer future to significantly increase the effectiveness of their intake to improve the health state in people, to prolong their active life, and to strengthen the Ukrainian nation genetic fund.
Keywords: оздоровче харчування; health nutrition; нутриціологія; nutritionology; нутригеноміка; nutrigenomics; нутригенетика; nutrigenetics; персоналізоване харчування; personalized nutrition; геном; genome; кафедра іноземних мов професійного спрямування; кафедра технології оздоровчих продуктів